2019
DOI: 10.1177/1179550619881131
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Dysphagia From Hardware Migration After Anterior Cervical Discectomy and Fusion: An Unusual Cause and Review of Literature

Abstract: Post-operative dysphagia is the most common complication following anterior cervical discectomy and fusion (ACDF), with reports varying from 1% to 79%. We report a case of a 63-year-old female patient complaining of dysphagia presenting 9 years post surgery. The cause of dysphagia is often multifactorial with the true aetiology poorly understood. One potentially life-threatening cause of post-operative dysphagia is hardware migration associated with pharyngoesophageal perforation. This patient presents a uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Over‐manipulation of fixation devices to fit patient‐specific contours, individual implant defects, and unequally applied forces by the muscles of mastication can contribute to hardware failure. Hardware failures may manifest as loose screws, migration of fixation devices through adjacent tissues, or plate fractures 53,57 . Plate fracture is unusual outside the setting of previous radiotherapy treatment and ORN 58 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over‐manipulation of fixation devices to fit patient‐specific contours, individual implant defects, and unequally applied forces by the muscles of mastication can contribute to hardware failure. Hardware failures may manifest as loose screws, migration of fixation devices through adjacent tissues, or plate fractures 53,57 . Plate fracture is unusual outside the setting of previous radiotherapy treatment and ORN 58 .…”
Section: Resultsmentioning
confidence: 99%
“…Hardware failures may manifest as loose screws, migration of fixation devices through adjacent tissues, or plate fractures. 53,57 Plate fracture is unusual outside the setting of previous radiotherapy treatment and ORN. 58 Management of hardware failure varies with the severity of the complication.…”
Section: Consensus Termsmentioning
confidence: 99%
“…Delayed-onset dysphagia may be variously attributed to: mass effect exerted on the posterior laryngeal wall by an abscess, delayed instrumentation failure with pharyngeal versus esophageal defect, [2] Fryer et al recently reported a case of hardware failure post-ACDF associated with dysphagia; [3] our case had clear ventral screw migration.…”
Section: Discussionmentioning
confidence: 59%
“…Screw loosening and plate migration in the anterior cervical discectomy fusion (ACDF) is not rare (Ning et al, 2008;Guo et al, 2021), even though hardware failure attributed to ACDF was demonstrated only 0.1%-0.9% in the United States (Epstein, 2019). Many clinical case reports revealed that screw loosening and anterior cervical plate migration happened in ACDF (Azadarmaki and Soliman, 2014;Nathani et al, 2015;Wójtowicz et al, 2015;Fryer et al, 2019;Ansari et al, 2020). Screw loosening in ACDF is one of the most dangerous complications in cervical anterior plating fixation, which may lead to severe consequences such as esophageal perforation and bone nonunion (Ning et al, 2008;Hershman et al, 2017;Fryer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many clinical case reports revealed that screw loosening and anterior cervical plate migration happened in ACDF (Azadarmaki and Soliman, 2014;Nathani et al, 2015;Wójtowicz et al, 2015;Fryer et al, 2019;Ansari et al, 2020). Screw loosening in ACDF is one of the most dangerous complications in cervical anterior plating fixation, which may lead to severe consequences such as esophageal perforation and bone nonunion (Ning et al, 2008;Hershman et al, 2017;Fryer et al, 2019). Therefore, prompt recognition and effective foreseeing of the potential pharyngoesophageal perforation would be pretty helpful in reducing the mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%